Exploring trait and task self-awareness in the context of leadership development among undergraduate students from Malaysia - Krauss, Steven Eric; Abdul Hamid, Jamaliah; Ismail, Ismi Arif (Sage Publications, 2010)
Despite the theoretical justification for the importance of self-awareness as a key input to leadership development, the construct, as understood according to awareness of one’s traits and tasks, has received little attention in the literature related to undergraduate leadership development. This article sets out to address this gap by investigating Trait and Task Self-awareness (SA) among more than 1700 undergraduate students from Malaysian institutions of higher learning. Analysis focused on comparing Trait and Task SA according to seven demographic variables. Results indicated that older, male students with higher CGPAs from the social sciences scored higher on both types of self-awareness than their counterparts. The findings begin to shed light on Malaysian undergraduates’ status in terms of the development of self-awareness in the context of leadership, and how it can be further enhanced.